(untitled) (Global Journal of Human-Social Science, 2018)
This Research paper is on the perception of male students in Dhaka University. Furthermore, those data analyzed about what is the perception of male students and how this construct. In this research, I explored the various approaches of male students to the female body and female attire. Moreover discussed how this approaches or perceptions constructed through their family moral values education, socialization, and circumstances. In qualitative research method, depth interview was taken from non-random sampling. Every interview was tape-recorded and transcribed very carefully. And analyze them after transcribing. And the result found that the male perception is closely related to their social learning and perception of sexuality and religious factor.